The role of the state in the development of tourism. The case of travel vouchers in Romania - Gheorghe CHEIA (Georeview, 2022)
The present paper analyzes, in the first part, the role that states/governments can have in the direction of the development of the tourism phenomenon in a certain country. This direction can be of at least two categories: direct and indirect. The state is mainly responsible for enabling an official legislative framework in which each participant in the tourism phenomenon has a well defined role and place, but also generates the promotion campaigns, opens special financing lines for tourism companies, offers different fiscal facilities, directly finances the specialization of employees in different sectors, and also makes general infrastructure and utilities available to citizens. Several cases of such interventions are presented and it is observed how different factors can cause problems in the implementation of these initiatives or even in not achieving the expected results. A more widely analyzed example is that of Romania, an EU member country since 2007, which over time pursued the launch and promotion of tourism as a profitable economic branch through various methods: legislative, financial, fiscal and, for several years, through the voucher system travel cards used on a nationally scale. The effect of the latter can be observed in the national flows and in the degree of occupancy of accommodation units. Using the data from the website of the Statistics Institute, a direct and comparative analysis is made (between different time periods, when these vouchers did not exist and the immediately following period when they were issued and used) of different tourist indices, with the aim of assessing the impact of this method on the development of the tourist sector in Romania.